Heat Shock Proteins 70 Regulate Cell Motility and Invadopodia-Associated Proteins Expression in Oral Squamous Cell Carcinoma - Ding, Le-Xi; Zhang, Jing; Yang, Si-Si; Wu, Jin; Su, Tong; Wang, Wei-Ming (Frontiers in Endocrinology, 2022)
Background: Many studies have shown that diabetes is often closely related to oral squamous cell carcinoma (OSCC) occurrence and metastasis. Heat shock protein 70 (Hsp70) is a molecular chaperone related to diabetes complications. This study aims to investigate the role of heat shock proteins 70 (Hsp70) in OSCC in expression of invadopodia-associated proteins. Methods: The expressions and correlation of HSP70, Hif1α, MMP2, MMP14 and cortactin were examined using bioinformatics analysis and verified by OSCC tissue microarrays. Assay in vitro were performed to analyze cell migration capacity after treatment with or without the HSP70 inhibitor. Results: The expressions of invadopodia-associated proteins were enhanced in OSCC tissues compared with paracarcinoma tissues and partially correlated with HSP70. Inhibiting HSP70 significantly decreased the cell viability, proliferation, migration of OSCC cells. Conclusions: HSP70 may be involed in invadopodia-associated proteins in OSCC cells, which provides a promising method for treatment of OSCC metastasis.